Pathway of Glucose Fermentation in Relation to the Taxonomy of Bifidobacteria - de Vries, Wytske (1967)
Cell-free extracts of 17 strains of Bifidobacterium bifidum (Lactobacillus bifidus) were examined for the presence of aldolase, glucose-6-phosphate dehydrogenase, and fructose-6-phosphate phosphoketolase. All strains turned out to lack aldolase, an enzyme unique to glycolysis, and glucose-6-phosphate dehydrogenase, characteristic of the hexosemonophosphate pathway. In all strains, fructose-6-phosphate phosphoketolase could be demonstrated. It can be concluded that bifidobacteria ferment glucose via a pathway which is different from those found in members of the genus Lactobacillus. The results strengthen the previous suggestions that classification of the bifidobacteria in the genus Lactobacillus is not justified.